Nigeria-Turkey Relations: An Overview - Bashir, Hamman Abubakar (European Scientific Journal, ESJ, 2018)
Interests of sovereign states trancends beyond friendships of individuals and commonalities in cultures or believes. Over the years, Turkey’s foreign policy has impacted on many African nations in many ways. It is either trying to compete with other powerful nations such as China and India or participating in Humanitarian activities in places such as Somalia, Sudan and Niger. Moreso there seems to be a need to analyse the interest of Turkey in one of Africa’s most powerful countries, and Turkey’s close ally in Africa, Nigeria. It has been a century of codial relationship between the two countries, before the major diplomatic down-turn that occured after the failed coup attempt in Turkey. The paper also tries to analyse the AKP foreign policy toward Nigeria. Therefore, this paper analyses the relationship and interests of Turkey in Nigeria. The paper will analyse why the choice of Nigeria and not other countries around it. It will also critically discuss the strategies and failures of Turkish foriegn policy in Nigeria.The study uses the qualitative research method by critically analysing previous, relevant studies published in journals, books, conference proceeds and so on, as well as media reports. Propositions in this study are based on foreign policy perspective as the theoretical framwork. Findings show that the relationship between the two countries dates back to the Ottoman era. The paper tries to explore the origin and development of the relationship over the years.As the paper reflects from a foriegn policy perspective, it will analyse factors that form substance of the foreign policy analysis.